Penerapan RESTful API untuk Membangun Program Pembayaran Piutang Menggunakan Otentikasi OAuth 2.0 - Nina Wulandari; Argo Wibowo; Budi Susanto (Fakultas Teknologi Informasi, 2021)
Retail business competition which is increasingly fast requires businesses to have a product sales strategy that is able to compete. Amigo Group convert this strategy by providing account receivable services for customers. The study